2017
DOI: 10.3934/publichealth.2017.5.466
|View full text |Cite
|
Sign up to set email alerts
|

Team Sport in the Workplace? A RE-AIM Process Evaluation of ‘Changing the Game’

Abstract: BackgroundThe workplace is a priority setting to promote health. Team sports can be an effective way to promote both physical and social health. This study evaluated the potential enablers and barriers for outcomes of a workplace team sports intervention programme ‘Changing the Game’ (CTG). This study was conducted in a FTSE 100 services organisation. This process evaluation was conducted using the RE-AIM framework.MethodsA mixed methods approach was used. Data were collected from the participants in the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Similar barriers and facilitators have been reported in previous work from public and private sector organisations (e.g. 53,56,57), however as such factors are likely to be highly setting specific (16), it remains vital to explore them in the environment where an intervention is to be implemented.…”
Section: Discussionmentioning
confidence: 55%
“…Similar barriers and facilitators have been reported in previous work from public and private sector organisations (e.g. 53,56,57), however as such factors are likely to be highly setting specific (16), it remains vital to explore them in the environment where an intervention is to be implemented.…”
Section: Discussionmentioning
confidence: 55%
“…Overall, results indicate that the program reached 66% of shift workers in the company. The proportion of participants signing up for our study was higher than other workplace health promotion programs, with the reach ranging from 23% to 59% [ 32 , 47 , 48 ]. The proportion of workers enrolled in our study suggested that the strategy of using several recruitment strategies was successful.…”
Section: Discussionmentioning
confidence: 83%
“…Evidence shows that organisational management support during the recruitment for workplace health promotion programs result in enhanced participation [ 49 ]. In a study with low recruitment rates, participants reported that the program had not been effectively communicated by the management teams [ 32 ]. To improve future study participation rates, it may be important to prioritise management involvement to encourage workers to participate in health promotion programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation